A comprehensive education of sexuality from psychosocial skills in Cuban adolescents - Benitez Olivera, Noel; García Quintero, Estrella; Amayuela Mora, Georgina (Transformación, 2024)
Objective: This article aims at exploring the particular features of the process of comprehensive sexual education from psychosocial skills in Cuban adolescents.Methods: The authors rely on historical-logical, analytical-synthetic methods, as well as on documentary analysis and interviewing key informants. The guidelines of the query were the individual concept of sexual education, the selection of for the education of sexuality in connection to psychosocial skills training and the procedures followed in teenagers’ sexual education.Results: The study revealed the stages and trends in the historical process of comprehensive sexual education in connection to psychosocial skills in Cuban adolescents, as well as the main features that characterized each of them.Conclusion: The awareness of psychosocial skills importance as a component of the process of comprehensive sexual education of adolescents in Cuba is at an initial stage. The recognition of its importance starts by the closing decade of the twentieth century. It is now moving from a spontaneous, non-systematic and fragmented character to the institutionalization of sexual education as a curricular axis.
Keywords: adolescence; comprehensive sexuality education; psychosocial skills sexual behavior; basic skills